Memahami Prinsip Kerja Kapitalisme dalam Invasi Rusia terhadap Ukraina - Alfian Tri Laksono; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
The world political situation is sometimes difficult to predict. Tensions between major countries often raise global concerns which are feared to trigger collective chaos which seriously endangers human existence on this earth. However, what do you mean by these concerns